Study of agro behavior technological and selection of seven varieties of durum wheat (Triticum durum Dest.) cultivated in zone sub wet (Smar Wad) , Algeria. - ojs_admin; Hamid, Kadhum (University of Thi-Qar Journal of Science, 2019)
The objective is to study the behavior of 7 varieties of durum wheat, under sub-humid climate (soft and rainy winter and dry and hot summer) and a clay soil and weak organic matter rates. Among the 7 varieties, 5 are from France and 2 from Algeria. During the vegetation’s growth, we studied the biological parameters for each variety in the laboratory of the Institute of Agriculture of Blida (Algeria) in 2005 and the results were interpreted statistically. The best results were given by V2, V3, and V4 in terms of grains number and V5 in terms of quality.